Effect of the Use ofIndigenous Language in Nigeria’s Advertisement: A Study of Milk Billboard in Lagos State - Chima-Omeike, Ogechi Joan; Taiwo, Adebisi (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
Advertisment is an indispensable tool for producers and marketers of goods and services all over the world. Language is one of the most important element for a successful advert to take place. It important for the target audience to understand the message that is being passed across in order to achieve its ultimate objective which is to increase sales and maximize profit through its target market. The objective of this study is to examine the effect of advertising with the use of indigenous languages in Nigeria, which is a country with several tribes and ethnic groups. Peak Milk Billboard advertisement in Lagos State in Hausa Language was used as case study and quantitative method with the use of questionnaire as research instrument was used to determine the effect of the use of indigenous languages for advertising in a multi tribal country like Nigeria. Findings revealed that the use of the language which is different from the language of the location will not appeal to those that reside in that area. It was recommended that further research be done to achieve a more solid supposition.